Crizanlizumab and comparators for adults with sickle cell disease: a systematic review and network meta-analysis. Issue 9 (17th September 2020) - Thom, Howard; Jansen, Jeroen; Shafrin, Jason; Zhao, Lauren; Joseph, George; Cheng, Hung-Yuan; Gupta, Subhajit; Shah, Nirmish
Abstract : Objectives: Treatment options for preventing vaso-occlusive crises (VOC) among patients with sickle cell disease (SCD) are limited, especially if hydroxyurea treatment has failed or is contraindicated. A systematic literature review (SLR) and network meta-analysis (NMA) were conducted to evaluate the efficacy and safety of crizanlizumab for older adolescent and adult (≥16 years old) SCD patients. Methods: The SLR included randomised controlled trials (RCTs) and uncontrolled studies. Bayesian NMA of VOC, all-cause hospitalisation days and adverse events were conducted. Results: The SLR identified 51 studies and 9 RCTs on 14 treatments that met the NMA inclusion criteria. The NMA found that crizanlizumab 5.0 mg/kg was associated with a reduction in VOC (HR 0.55, 95% credible interval (0.43, 0.69); Bayesian probability of superiority >0.99), all-cause hospitalisation days (0.58 (0.50, 0.68); >0.99) and no evidence of difference on adverse events (0.91 (0.59, 1.43) 0.66) or serious adverse events (0.93 (0.47, 1.87); 0.59) compared with placebo. The HR for reduction in VOC for crizanlizumab relative to L-glutamine was (0.67 (0.50, 0.88); >0.99). These results were sensitive to assumptions regarding whether patient age is an effect modifier. Conclusions: This NMA provides preliminary evidence comparing the efficacy of crizanlizumab with other treatments for VOC prevention.